Islamic Spiritual Counseling for The Elderly: Preparing for A Righteous Death (Husnul Khotimah) at Nursing Home X in Cirebon - Rina Kurnia; Faika Maudina (Proceedings Of International Conference On Islamic Counseling Studies (ICONICS), 2025)
This study focuses on Islamic spiritual counseling for elderly residents at Nursing Home X in preparing for a righteous death (husnul khotimah). In Islam, death is perceived as a transition to the afterlife; therefore, it is essential for Muslims to engage in spiritual preparation. The elderly phase of life, marked by physical and mental decline, poses significant psychological challenges, including anxiety and loneliness. Utilizing a qualitative approach and narrative method, this research explores the implementation of spiritual counseling comprising Qur’anic recitation, dhikr (remembrance of God), and religious sermons and its impact on the elderly’s readiness for death. The findings reveal that these activities not only strengthen the elderly’s spiritual connection with Allah SWT but also foster inner peace and a sense of hope. Elderly individuals who participated in the spiritual counseling reported increased mental preparedness for death and a heightened sense of mutual support among fellow residents. Islamic spiritual counseling serves as a vital instrument in enhancing the elderly’s quality of life, enabling them to experience old age with greater meaning and serenity. These findings emphasize the necessity of integrating spiritual counseling into elder care programs at Nursing Home X to support their psychological and spiritual well-being.